Association Between Asthma and Migraine: A Systematic Review and Meta-Analysis of Observational Studies - Kang, Lin-Lin; Chen, Pei-En; Tung, Tao-Hsin; Chien, Ching-Wen (Frontiers in Allergy, 2021)
Objectives: The purpose of this study was to determine the association between asthma and migraine and assess the risk for migraine in patients with asthma. Methods: We systematically searched the Cochrane Library, PubMed, MEDLINE, and EMBASE databases from inception to 26th September 2021 for indexed observational studies that examined either the odds or risk of migraine in subjects with asthma. The qualities of the included studies were evaluated using the Newcastle-Ottawa Scale. A random-effects meta-analysis was performed to calculate the odds ratio for case-control and cross-sectional studies and the risk ratio for cohort studies. Results: Seven observational studies (four cross-sectional and three cohort studies) with a total of 549,534 study subjects were included in this systematic review and meta-analysis and selected for data extraction. Four articles were considered to be of moderate-quality; other studies were considered to be of high-quality. Asthma was associated with increased odds (OR, 1.85; 95%CI, 1.39-2.45) and risk of migraine (RR, 1.70; 95%CI, 1.52-1.90). Conclusions: The available evidence that supports the existence of an association between asthma and migraine is limited. Clinicians should be aware that patients with asthma show both increased prevalence and incidence of migraine. Further studies are warranted to clarify the relationship between asthma and migraine further.